Jurisdiction Expansion as a Examination of the Indonesian Constitutional System in Receiving Reports on the Alleged Rohingya Genocide at the Attorney General's Office of the Republic of Indonesia - Lio Widodo; Avivah Firisqi Leksono (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
The development of international law has expanded state jurisdiction beyond territorial boundaries through the application of universal jurisdiction over international crimes, particularly genocide. This development has created constitutional and legal challenges in Indonesia following the submission of a report to the Attorney General’s Office concerning alleged genocide against the Rohingya in Myanmar, although the alleged crimes occurred outside Indonesia’s territorial jurisdiction. This situation reflects the tension between the international obligation to combat impunity and the constitutional principle of legality governing the exercise of state authority. This study aims to examine the implications of universal jurisdiction for Indonesia’s constitutional system, particularly regarding state sovereignty and the constitutional limits of law enforcement authority. The research employs a normative legal method using statutory and conceptual approaches supported by primary and secondary legal materials. The findings reveal that, although Indonesia has adopted several principles of international criminal law, universal jurisdiction has not yet been explicitly recognized in national legislation. The study also identifies conceptual ambiguity in distinguishing universal jurisdiction under international law from jurisdictional principles in Indonesian criminal law, resulting in legal uncertainty. From a constitutional perspective, exercising criminal jurisdiction without an explicit statutory basis risks exceeding the authority of state institutions and undermining legal certainty. This study concludes that the implementation of universal jurisdiction in Indonesia requires explicit legislative authorization. Therefore, amendments to the Human Rights Court Law or the enactment of specific legislation governing universal jurisdiction are necessary to ensure constitutional legitimacy, strengthen legal certainty, and maintain consistency with the principles of the rule of law and state sovereignty.